Derechos sobre el uso de la tierra para la tierra agrícola en Ucrania - Dmytro Fedchyshyn; Iryna Ignatenko; Liudmyla Leiba (Ius Humani. Jornal do direito, 2020)
The article deals with the rights to agricultural land under the conditions of the moratorium on the alienation of agricultural land in Ukraine. Currently land lease is the most widespread land-use right in Ukraine. The purpose of the article is to investigate the features and prospects of the functioning of the land market in Ukraine and to increase investor interest in it. The dialectical method made it possible to consider the development of land-use rights in Ukraine, to formulate proposals for improving existing legislation. The method of comparative legal analysis made it possible to compare the system of relations of land ownership and lease in Ukraine and other countries of the world. Much attention has been paid to the abolition of the moratorium on the purchase of agricultural land in Ukraine, which will lead to a gradual increase in the share of entrepreneurial activity on owned land with an optimal ratio of land lease. Based on the features of agricultural land lease, the following positive points are highlighted: 1) the availability of long-term lease guarantees the tenant’s stability in land use and promotes better planning and investment attractiveness; 2) the ability to set a fixed size of land rent without taking into account the normative monetary valuation; 3) rents for agricultural land in Ukraine continue to be much lower than in other countries.